EVALUATION OF ADAPTATIVE RESOURCES OF CHILDREN WITH MODERN AUTOMATED TECHNOLOGY - V.N. Luchaninova; L.V. Trankovskaya; E.A. Kosnitskaya ("Paediatrician" Publishers LLC, 2008)
Adaptative resources of children's organisms at the time of their entrance to school were evaluated with modern automated technology - the method of computer dermographia (KD). Significant risk factors of negative course of adaptative process were determined. High self descriptiveness of KD for integral estimation of state of health at the time of adaptation of children to the school conditions was demonstrated. The scheme of prophylactic measures was developed for the purpose of improvement of state of health of children in preschool age and minimization of negative effects of adaptational period.Key words: adaptation, first formers, computer dermographia.